Microbial Mechanisms for Remediation of Hexavalent Chromium and their Large-Scale Applications; Current Research and Future Directions - Amr Arishi; Ibrahim Mashhour (Journal of Pure and Applied Microbiology, 2021)
The increase of anthropogenic activities has led to the pollution of the environment by heavy metals, including chromium (Cr). There are two common oxidative states of Cr that can be found in industrial effluents the trivalent chromium Cr(III) and the hexavalent chromium Cr(VI). While the hexavalent chromium Cr(VI) is highly toxic and can trigger serious human health issues, its reduced form, the trivalent chromium Cr(III), is less toxic and insoluble. Leather tanning is an important industry in many developing countries and serves as a major source of Cr(VI) contamination. Globally, tannery factories generate approximately 40 million m3 of Cr-containing wastewater annually. While the physico-chemical treatments of tannery wastewater are not safe, produce toxic chemicals and require large amounts of chemical inputs, bioremediation using chromium-resistant bacteria (CRB) is safer, efficient and does not produce toxic intermediates. Chromium-resistant bacteria (CRB) utilise three mechanisms for Cr(VI) removal: biotransformation, biosorption and bioaccumulation. This review will evaluate the three Cr(VI) detoxification mechanisms used by bacteria, their limitations and assess their applications for large-scale remediation of Cr(VI). This can be helpful for understanding the nature of Cr(VI) remediation mechanisms used by bacteria, therefore, bridging the gap between laboratory findings and industrial application of microorganisms for Cr(VI) removal.